2020
DOI: 10.1002/bbb.2152
|View full text |Cite
|
Sign up to set email alerts
|

Genetic manipulation of non‐solvent‐producing microbial species for effective butanol production

Abstract: Butanol is widely used as an important bulk chemical and is a potential biofuel. The depletion of fossil fuels and advances in synthetic biotechnology have led to renewed interest in the biological production of butanol. Solventogenic Clostridium was commonly used to produce butanol through traditional acetone‐butanol‐ethanol (ABE) fermentation. However, its relatively slow growth rate, low butanol tolerance, and poor production efficiency have hindered the further application of this procedure. Recently, othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Butanol is a sustainable technology for alternate and renewable energy, being less corrosive and with higher energy content per unit mass than traditional fuels. The butanol potential includes its use as a solvent and a platform chemical in the cosmetic and pharmaceutical industry (Lv et al, 2021).…”
Section: Genes Involved In Antimicrobial Activities or Important Enzymes For Industrymentioning
confidence: 99%
“…Butanol is a sustainable technology for alternate and renewable energy, being less corrosive and with higher energy content per unit mass than traditional fuels. The butanol potential includes its use as a solvent and a platform chemical in the cosmetic and pharmaceutical industry (Lv et al, 2021).…”
Section: Genes Involved In Antimicrobial Activities or Important Enzymes For Industrymentioning
confidence: 99%
“…E. coli, P. putida) [48,49]. A more detailed review on non-solvent-producing hosts can be found elsewhere [50]. Another challenge Clostridium species face is their glucose requirements and low ability to degrade other sugars and carbohydrates.…”
Section: Challenges In Biobutanol Productionmentioning
confidence: 99%